Fitness cost and compensation mechanism of sulfonamide resistance genes ( sul1 , sul2 , and sul3 ) in Escherichia coli - Yuqiao Zhou; Jiehong Fang; Zaeim Davood; Jianzhong Han; Daofeng Qu (Environmental Microbiology, 2021)
Summary The fitness cost of antibiotic resistance is a crucial factor to determine the evolutionary and transmission success of resistant bacteria. Exploring the fitness cost and compensation mechanism of antibiotic resistance genes (ARGs) in bacteria may effectively reduce the transmission of drug‐resistant genes in the environment. Engineered bacteria with the same genetic background that carry sulfonamide resistance gene were generated to explore the fitness cost of sulfonamide resistance gene in Escherichia coli . There were significant differences in the protein expression of the two‐component system pathway ( fliZ , fliA , fliC and lrhA ), folate biosynthesis pathway ( sul1 , sul2 and sul3 ), ABC transporter system ( ugpC , rbsA and gsiA ), and outer membrane pore protein OmpD through the comparative analysis of differential proteins compared to sensitive bacteria. Thus, we could speculate the possible fitness compensation mechanism. Finally, quantitative Real‐time PCR (qRT‐PCR) was used to verify the functions of some differential proteins at the transcriptional level. The fitness cost and compensatory evolution of antibiotic resistance are an essential part of bacterial evolution.